Results of Giltsrearing in Outdoor Production System - Alexy, Márta; Nagy, Géza; Gundel, János (Acta Agraria Debreceniensis, 2003)
The applied technology is an alternative approach to pigkeeping-systems. An outdoor pig production breeding sows are kept at pasture either year-round or in a certain period of the year. The important equipments of outdoor pig production are farrowing or grouping sows inhuts, which protect pigs against the effects of extreme weather, and electric fences, which surround and divide the pasture. Concentrate feed can be fed from the ground or from feeders which are made of steel or timber. One of main advantages of this pig keeping system is the total mobilizable keeping technology.Within the scope of the study we are performing an experiment to make a comparison between coventional system and free range sows keeping technology. Pannonhybrid F1 gilts were used in this experiment, 28 gilts were kept on pasture all day and 28 gilts are kept in conventional, indoor system.In this work the results of gilts-rearing are presentated as a part of our two-years experiment.